Isolation, Molecular Detection, and Risk Factors of Campylobacter Infection From Companion Dogs - Darioush Gharibi (Alborz University of Medical Sciences, 2020)
Background: Campylobacter is an organism that is usually associated with diarrhea in pet animals and humans, as well as other domestic, wild, and laboratory animals. Objective: The aim of the present survey was the isolation, molecular detection, and risk factors of Campylobacter infection from companion dogs referred to the Veterinary Hospital of Ahvaz district, the South-West of Iran. Materials and Methods: Rectal swabs were examined by culture and polymerase chain reaction (PCR) methods from 122 companion dogs (52 diarrheic and 70 clinically healthy). Several risk factors were reviewed, including age, gender, breed, nutrition status, and lifestyle. Results: The results showed that only five samples (4.1%) were positive for Campylobacter spp. in the culture method. Campylobacter spp. was detected in 18 out of 122 dogs by the PCR, yielding an overall prevalence of 14.8%. The most prevalent species of Campylobacter among the referred dogs were C. coli (38.89%) and C. jejuni (33.33%). A lower prevalence was found for C. upsaliensis (11.11%) and C. lari (5.55%). Concurrent infections were observed in two cases of C. upsaliensis + C. lari (5.55%) and C. coli + C. lari (5.55%). No significant difference was noted between healthy (11.43%) and diarrheic (19.23%) dogs (P>0.05). Eventually, age, gender, breed, nutrition status, and lifestyle had no significant effect on Campylobacter infection (P>0.05). Conclusion: Although the prevalence of Campylobacter was moderate in the dog population of Ahvaz district, these bacteria can constitute a public health hazard because of the frequent presence of Campylobacter species in the feces.